2009
DOI: 10.1007/s12193-009-0027-3
|View full text |Cite
|
Sign up to set email alerts
|

From expressive gesture to sound

Abstract: This paper contributes to the development of a multimodal, musical tool that extends the natural action range of the human body to communicate expressiveness into the virtual music domain. The core of this musical tool consists of a low cost, highly functional computational model developed upon the Max/MSP platform that (1) captures real-time movement of the human body into a 3D coordinate system on the basis of the orientation output of any type of inertial sensor system that is OSC-compatible, (2) extract lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…Research has shown that these body movements often reflect the performer's movements from which the music originated (Leman et al, 2009; Godøy and Leman, 2010), certain aspects of the melody, harmony, rhythm and timbre (Maes et al, 2010; Naveda and Leman, 2010; Toiviainen et al, 2010; Burger et al, 2013; Leman et al, 2013), or even the listeners' mood (Van Dyck et al, 2013). These and similar studies importantly indicate that the listeners' musical mind (attention, intention, mood, feelings, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that these body movements often reflect the performer's movements from which the music originated (Leman et al, 2009; Godøy and Leman, 2010), certain aspects of the melody, harmony, rhythm and timbre (Maes et al, 2010; Naveda and Leman, 2010; Toiviainen et al, 2010; Burger et al, 2013; Leman et al, 2013), or even the listeners' mood (Van Dyck et al, 2013). These and similar studies importantly indicate that the listeners' musical mind (attention, intention, mood, feelings, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…'The basic problem of these interfaces concerns the fact that the mediation between the different modalities (basically from movement to sound) has an arbitrary component, which is due to the fact that the energies of the modalities are transformed into electronic signals. This is in contrast with traditional instruments, where energetic modalities are mechanically mediated and where the user gets a natural feeling of the causality of the multimodal interface' [1].…”
Section: Choreography On the Electronic Kitmentioning
confidence: 95%
“…These three factors cannot coexist and hence must be weighed up against each other. Using these three factors, we outline our approach to the 'mapping problem' [1] in designing a new gestural instrument for electronic percussion. We use the analogy of a dancer choreographing her/his movement to prerecorded sound in taking a compositional approach to mapping, beginning with the music and working backwards to the choreography of the movement on the gestural instrument to best fit with the music.…”
Section: Introductionmentioning
confidence: 99%
“…Leveraging the above, there is a growing interest in the analysis of the gestural knowledge. A large amount of studies conducted in the last years on embodied music cognition have investigate that not only effective, but also accompanist and figurative gestures are very important, since they are related to the expressivity and to the social interaction of the performer with the audience [Jensenius 2007;Maes et al 2010]. However, "learning" musical gestures and "performing" music are usually perceived as separate concepts and experiences that pass through intermediate physical mechanisms.…”
Section: Conclusion From the State-of-the-art And Motivationmentioning
confidence: 99%